Is the omega sign a reliable landmark for the neurosurgical team? An anatomical study about the central sulcus region - Thiago Rodrigues; Mariana Rodrigues; Daniel Paz; Marcos Devanir Costa; Bruno Santos; Vinicius Braga; Manoel de Paiva Neto; Ricardo Centeno; Sergio Cavalheiro; Feres Chaddad-Neto (Arquivos de Neuro-Psiquiatria)
ABSTRACTThe central sulcus region is an eloquent area situated between the frontal and parietal lobes. During neurosurgical procedures, it is sometimes difficult to understand the cortical anatomy of this region.Objective Find alternative ways to anatomically navigate in this region during neurosurgical procedures.Method We analyzed eighty two human hemispheres using a surgical microscope and completed a review of the literature about central sulcus region.Results In 68/82 hemispheres, the central sulcus did not reach the posterior ramus of the lateral sulcus. A knob on the second curve of the precentral gyrus was reliably identified in only 64/82 hemispheres.Conclusion The morphometric data presented in this article can be useful as supplementary method to identify the central sulcus region landmarks.